2020
DOI: 10.37899/journallalifesci.v1i5.244
|View full text |Cite
|
Sign up to set email alerts
|

Endo-Helminth Fauna of the Rainbow Lizard (Agama Agama)

Abstract: This parasitological study was carried out between February and May 2019 to determine the prevalence and intensity of helminthiasis in the rainbow lizard (Agama agama) in Okrika, Rivers State, Nigeria. A total of one hundred and fifty-one (151) specimens made up of 93 males and 75 females were caught by a local netting system during the day and anaesthesized with chloroform. Samples were collected from two stations (Ogoloma-Ama and Oba-Ama). After dissection, the esophagus, stomach, small intestine, rectum, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With at least 37 species distributed across Africa, primarily in sub-Saharan regions, these reptiles vary in size, typically reaching 12 to 30 centimeters when fully grown [1]. Lizards, one of the most widely distributed reptiles globally, demonstrate remarkable adaptability across various habitats [2]. However, this study revolves around the Agama agama lizard, a species known to be a means of transport and reservoir host for helminth and protozoan parasites, thereby raising significant concerns [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With at least 37 species distributed across Africa, primarily in sub-Saharan regions, these reptiles vary in size, typically reaching 12 to 30 centimeters when fully grown [1]. Lizards, one of the most widely distributed reptiles globally, demonstrate remarkable adaptability across various habitats [2]. However, this study revolves around the Agama agama lizard, a species known to be a means of transport and reservoir host for helminth and protozoan parasites, thereby raising significant concerns [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study revolves around the Agama agama lizard, a species known to be a means of transport and reservoir host for helminth and protozoan parasites, thereby raising significant concerns [3]. In Nigeria, comprehensive investigations by Robert et al, [2], Akinboade and Johnson [4], and Wekhe and Olayinka [3] have identified the prevalence of protozoan parasites such as Eimeria oocysts, Plasmodium, and Haemogregarina species, with Eimeria oocysts being the most prevalent (68.7%).…”
Section: Introductionmentioning
confidence: 99%